A6_3 Traveling to the Future - Bristowe, Thomas; Pizarro Salcedo, Claudio; Price, Tom; Gorringe, Peter (Physics Special Topics, 2021)
In the special theory of relativity, a moving clock runs slow. This means that if a person was to move at high speeds away from earth and then eventually return, they would have aged less than someone stationary on the earth. In this paper, we determine the maximum theoretical amount of time the average person could travel to the future using this method and the velocity of the person as a function of the persons proper time as they take the trip. We found that the furthest a person could travel to the future is 267 million years. However, even an increase by just 10% to either the time of the trip by the persons perspective or to the acceleration can turn this answer from hundreds of millions of years to billions of years.